2021
DOI: 10.1038/s41390-021-01641-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between secondhand marijuana smoke and respiratory infections in children

Abstract: BACKGROUND:Little is known about the effects of secondhand marijuana smoke on children. We aimed to determine caregiver marijuana use prevalence and evaluate any association between secondhand marijuana smoke, childhood emergency department (ED) or urgent care (UC) visitation, and several tobacco-related illnesses: otitis media, viral respiratory infections (VRIs), and asthma exacerbations. METHODS: This study was a cross-sectional, convenience sample survey of 1500 subjects presenting to a pediatric ED. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The limited data available, however, suggest that cannabis consumption may be associated with alterations to mucosal microbial profiles [ 19 ]; the development of a diverse non- Lactobacillus -predominant vaginal microbiota [ 20 ]; an altered oral microbiome with an enhanced Streptococcus and Actinomyces and depressed Neisseria content [ 21 ]; risk of sexually transmitted disease in men [ 22 ]; seropositivity for hepatitis C virus [ 23 ]; and increased risk of fungal infections [ 24 ]. Moreover, Johnson et al have recently reported that environmental exposure to cannabis smoke in children increases the likelihood of viral respiratory diseases [ 25 ]. Therefore, there is a clear need for a greater understanding of any potential relationships between cannabis use and microbial-induced diseases.…”
Section: The Antimicrobial Properties Of Cannabis and Cannabis-derive...mentioning
confidence: 99%
“…The limited data available, however, suggest that cannabis consumption may be associated with alterations to mucosal microbial profiles [ 19 ]; the development of a diverse non- Lactobacillus -predominant vaginal microbiota [ 20 ]; an altered oral microbiome with an enhanced Streptococcus and Actinomyces and depressed Neisseria content [ 21 ]; risk of sexually transmitted disease in men [ 22 ]; seropositivity for hepatitis C virus [ 23 ]; and increased risk of fungal infections [ 24 ]. Moreover, Johnson et al have recently reported that environmental exposure to cannabis smoke in children increases the likelihood of viral respiratory diseases [ 25 ]. Therefore, there is a clear need for a greater understanding of any potential relationships between cannabis use and microbial-induced diseases.…”
Section: The Antimicrobial Properties Of Cannabis and Cannabis-derive...mentioning
confidence: 99%
“…Cannabis smoking releases many carcinogens, with some studies reporting that second-hand cannabis smoking (SHCS) is associated with increased heart rate, a "pleasant" psychoactive effect, psychomotor and working memory impairment, as well as eye and mucous irritation (Holitzki et al, 2017;Wei et al, 2019). Some studies reported severe allergic reactions to SHCS by children and adolescents (Cabrera-Freitag et al, 2019;Hoffman et al, 2018) and cross-sectional surveys found an increased prevalence of: viral respiratory infections, ear infection, asthma, bronchitis/bronchiolitis; notably, among children of caregivers who smoke cannabis (Johnson et al, 2021;Posis et al, 2019).…”
Section: Second-hand Cannabis Smokingmentioning
confidence: 99%
“…Cannabis smoking releases many carcinogens, with some studies reporting that second‐hand cannabis smoking (SHCS) is associated with increased heart rate, a “pleasant” psychoactive effect, psychomotor and working memory impairment, as well as eye and mucous irritation (Holitzki et al., 2017; Wei et al., 2019). Some studies reported severe allergic reactions to SHCS by children and adolescents (Cabrera‐Freitag et al., 2019; Hoffman et al., 2018) and cross‐sectional surveys found an increased prevalence of: viral respiratory infections, ear infection, asthma, bronchitis/bronchiolitis; notably, among children of caregivers who smoke cannabis (Johnson et al., 2021; Posis et al., 2019). In addition, cannabinoids from SHCS can be detected among nonsmokers, which can constitute a problem for individuals in safety sensitive positions, workplaces enforcing zero‐tolerance policies or drivers intercepted on the road that may be tested positive for cannabis, but were not impaired (Herrmann et al., 2015; Holitzki et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to smokers, non-smokers who are exposed to tobacco smoke absorb nicotine and its metabolites. Secondhand smoke (SHS) exposure can cause respiratory infections, cancers, and periodontal diseases [2][3][4]. Nicotine can be found in all types of tobacco products and some foods at smaller doses.…”
Section: Introductionmentioning
confidence: 99%